Diminished cellular and humoral immunity in workers occupationally exposed to low levels of ionizing radiation - Godekmerdan, A; Ozden, M; Ayar, A; Gursu, MF; Ozan, AT; Serhatlioglu, S (Elsevier Science Inc, 2004)
Background. It has been reported that subgroups of T-lymphocytes are affected at different levels and different cell groups of immune system give different responses in individuals exposed to long-term ionizing radiation. The aim of this study was to investigate the effect of occupational exposure to low levels of ionizing radiation in selected indices of cellular and humoral immunity in radiology workers. Methods. Level of subgroups of peripheral blood lymphocytes, complements (C-3, C-4), and total immunoglobulins (IgG, IgA, IgM) were analyzed in 50 radiology workers occupationally exposed to low levels of ionizing radiation and 35 age-matched healthy controls. Results. CD4(+) T lymphocyte (T-helper) levels were determined as significantly low in radiology workers exposed to ionizing radiation compared with controls (P < 0.05). There were no statistically significant differences in groups in terms of other subgroups of lymphocytes (p > 0.05). In addition, levels of serum total IgG, IgA, IgM, C-3, and C-4 were determined as significantly lower in workers exposed to ionizing radiation compared with controls (p < 0.001). Total IgA and IgM levels in radiology workers who were smokers were determined as significantly lower compared with non-smoking radiology workers (p > 0.05). Conclusions. Levels of CD4(+) T lymphocytes and humoral immune response (total immunoglobulins and complements) were determined as weaker in workers exposed to low levels of ionizing radiation compared with controls, indicating the importance of taking appropriate measures to protect radiology workers from exposure to ionizing radiation and for these workers to avoid smoking. Further studies are needed for determining the appropriateness of periodic check-ups of immune functions and the most efficient and cost-effective ways of monitoring immune functions in radiology workers for detecting early changes in the immune system. (C) 2004 IMSS. Published by Elsevier Inc.
Keywords: ionizing radiation; cellular and immoral immunity; occupational exposure; smoking; total immunoglobins